Data for: Northward range extension for Durvillaea poha bull kelp: response to tectonic disturbance? - Vaux, Felix; Craw, Dave; Fraser, Ceridwen I.; Waters, Jonathan M. (Dryad, 2021)
Data for: Vaux F, Craw D, Fraser CI, Waters JM. (2021). Northward range
extension for Durvillaea poha bull kelp: response to tectonic disturbance?
Journal of Phycology. https://doi.org/10.1111/jpy.13179
Understanding the forces that shape species distributions is increasingly
important in a fast-changing world. Although major disturbance events can
adversely affect natural populations, they can also present new
opportunities, for example by opening up habitat for colonisation by other
lineages. Following extensive geographic sampling, we use genomic data to
infer a range extension following disturbance for an ecologically
important intertidal macroalgal species. Specifically, we genotyped 288
bull-kelp (Durvillaea) plants from 28 localities across central New
Zealand. All specimens from the North Island were expected to be D.
antarctica, but unexpectedly 10 samples from four sites were unexpectedly
identified as D. poha. Extensive sampling from the northern South Island
(105 samples at five locations) confirmed the absence of D. poha north of
the Kaikōura Peninsula. The North Island specimens of D. poha therefore
reveal a biogeographic disjunction, some 150 km northeast of the nearest
(South Island) population of this species. Based on strong geographic
correspondence between these North Island samples and historic
disturbance, we infer that tectonic upheaval, particularly
earthquake-generated landslides, likely extirpated local D. antarctica and
created an opportunity for a northward range expansion event by D. poha.
Close phylogenomic relationships between this new North Island population
and South Island samples supports a geologically recent northward
expansion, rather than a deeper evolutionary origin. These findings
indicate the potential of large-scale disturbances to facilitate sudden
biogeographic range expansions, and they emphasise the ability of genomic
analyses with fine-scale sampling to reveal long-lasting signatures of
past disturbance, dispersal and colonisation.
DNA was extracted and purified following the same method described in
Peters et al. (2020), except that the new Qiagen DNeasy Plant Pro DNA
extraction kit replaced the equivalent decommissioned Qiagen PowerPlant
Pro kit. Samples were used for genotyping-by-sequencing (GBS; Elshire et
al. 2011). 14 new D. poha samples were sequenced across three GBS
libraries, which contained a total of 340 Durvillaea southern bull-kelp
samples, plus 61 samples belonging to unrelated taxa. The GBS sequencing
followed an almost identical method to the previous studies (Parvizi et
al. 2020, Peters et al. 2020), with size selections varying between 200 –
500 bp and 200 – 600 bp. stacks 2.53 (Rochette et al. 2019) was
used to demultiplex samples into paired forward and reverse reads per
individual, call loci, and estimate genotypic variation among samples.
# north_island_d_poha_GBS # Stacks Shell files with commands and parameter
settings used for each STACKS run. # maps Maps used to select individuals
and populations in STACKS runs. # excluded_loci Lists used to exclude
certain loci in STACKS runs. # plink-ld Ped and map input files and shell
file with settings used by plink to estimate loci in LD. #
vcftools-highly-correlated Shell file with commands and the recoded VCF
files used to estimate highly correlated loci (additional filtering step
for alternative filtered dataset). Text file lists loci added for
alternative dataset excluded loci list. Includes input VCF file (i.e. main
filtered dataset). # vcftools-low-coverage Shell file with commands and
the recoded VCF files used to estimate low coverage genotypes and loci
(first filtering step). Text file lists loci added for first list of
excluded loci. # R R files for running loci filtering (e.g. loci coverage
depth outliers) and population genetic analyses (e.g. adegenet, LEA). I
recommmend viewing original source GitHub pages and tutorials noted in
each R file credits. Includes example R project and geno files for LEA
analyses. # Sampling, and genotype and loci fasta files Supplementary
tables, figures, methods and results (Appendix S1), full sample
details (Appendix S2), COI sequences (Appendix S3), GBS files (loci
consensus sequences, genotype files, phylogenetic alignments, trees) are
available here on DataDryad.  # Demultiplexed reads
Demultiplexed forward and reverse DNA sequence reads for the southern
bull-kelp sequenced in this study are openly available on the NCBI
sequence read archive (SRA) under: PRJNA683976,
http://www.ncbi.nlm.nih.gov/bioproject/683976 # Raw Illumina reads
Available on request, and we're working to archive all southern
bull-kelp raw reads on NCBI in the near future. # Further information See
this page: https://sites.google.com/view/evauxlution/data
Keywords: FOS: Biological sciences; Durvillaea; Durvillaea antarctica; Durvillaea poha; GBS (genotyping-by-sequencing); Biogeography